A multibit sigma-delta ADC for multimode receivers. - Miller, M.R (IEEE Journal of solid state circuits)
A 2.7-V sigma-delta modulator with a 6-bit quantizer is fabricated in a 0.18-μm CMOS process. The modulator makes use of noise-shaped dynamic element matching (DEM) and quantizer offset chopping to attain high linearity over a wide bandwidth. The DEM algorithm is implemented in such a way as to minimize additional delay within the feedback loop of the modulator, thereby enabling the use of the highest resolution quantizer yet reported in a multibit sigma-delta analog-to-digital converter of this speed. The part achieves 95-dB peak spurious-free dynamic range and 77-dB signal-to-noise ratio over a 625-kHz bandwidth, and consumes 30 mW at a sampling frequency of 23 MHz. The part achieves 70-dB signal-to-noise ratio over a 1.92-MHz bandwidth and dissipates 50 mW when clocked at 46 MHz.